Management of depressive symptoms in peri- and postmenopausal women: EMAS position statement - Stute, Petra; Spyropoulou, Areti; Karageorgiou, Vasilios; Cano, Antonio; Bitzer, Johannes; Ceausu, Iuliana; Chedraui, Peter; Durmuşoğlu, Fatih; Erkkola, Risto; Goulis, Dimitrios G.; Hirschberg, Angelica Linden; Kiesel, Ludwig; et al. (Elsevier, 2020)
Introduction: Globally, the total number of people with depression exceeds 300 million, and the incidence rate is 70 % greater in women. The perimenopause is considered to be a time of increased risk for the development of depressive symptoms and major depressive episodes. Aim: The aim of this position statement is to provide a comprehensive model of care for the management of depressive symptoms in perimenopausal and early menopausal women, including diagnosis, treatment and follow-up. The model integrates the care provided by all those involved in the management of mild or moderate depression in midlife women. Materials and methods: Literature review and consensus of expert opinion. Summary recommendations: Awareness of depressive symptoms, early detection, standardized diagnostic procedures, personalized treatment and a suitable follow-up schedule need to be integrated into healthcare systems worldwide. Recommended treatment comprises antidepressants, psychosocial therapies and lifestyle changes. Alternative and complementary therapies, although widely used, may help with depression, but a stronger evidence base is needed. Although not approved for this indication, menopausal hormone therapy may improve depressive symptoms in peri- but not in postmenopausal women, especially in those with vasomotor symptoms.
Keywords: Depression; Perimenopause; Menopausal Transition; Early Menopause; Menopausal Hormone Therapy; Model of Care; EMAS